Study of factors effecting indentation hardness index of natural latex foam - Sakulkaew, Kartpan; Saeju, Prasert (Bulletin of Applied Sciences, 2022)
Latex foam made from natural rubber latex has porous texture, good ventilation, and excellent load carrying capacity; therefore, it is widely used to make products such as pillows and mattresses. Indentation hardness index is one of the major properties that reflect the quality of latex foam products. This research aims to investigate the factors, affecting the indentation hardness index determined in accordance with TIS 2747-2559, and ISO 2439-2008, for example, density, thickness, location where the test pieces were obtained. This study has shown that these factors play a significant role in determining the indentation hardness index of the latex foam.